Giant solitary fibrous tumor of the lung: A case report. Issue 3 (May 2014) - Xiao, Ping; Sun, Linlin; Zhong, Diansheng; Lian, Linjuan; Xu, Dongbo
Abstract A solitary fibrous tumor arising from the lung parenchyma is rarely described. Here, we present the clinical, imaging, and histological features of a case of a 54‐year‐old woman with an incidental lung mass of the right lower lobe on a chest radiograph.